2007
DOI: 10.2174/156802607780059736
|View full text |Cite
|
Sign up to set email alerts
|

New Tuberculosis Drugs in Development

Abstract: Over the past 50 years, no new drug classes have been introduced to treat tuberculosis. Tuberculosis (TB) kills nearly two million people a year mainly in the poorest communities in the developing world. It afflicts millions more. About one third of the world's population is silently infected with TB that may erupt into disease with increased age or suppression of the immune system. Nearly nine million new active cases develop every year. The World Health Organization (WHO) declared the disease a global emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…A study with mycobacteria and other organisms showed excellent sensitivity (Х99%) and specificity (100%) and an appropriate detection limit (10 5 CFU/ml) when tested with M. tuberculosis H37Rv. This ICA can simplify the identification of M. tuberculosis in clinical laboratories.Tuberculosis is a global problem and the single most common cause of death from any bacterial agent (15,22). Mycobacterium tuberculosis and nontuberculous mycobacteria (NTM) are different clinically, so prompt detection, isolation, and discrimination are essential for appropriate management (3, 7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study with mycobacteria and other organisms showed excellent sensitivity (Х99%) and specificity (100%) and an appropriate detection limit (10 5 CFU/ml) when tested with M. tuberculosis H37Rv. This ICA can simplify the identification of M. tuberculosis in clinical laboratories.Tuberculosis is a global problem and the single most common cause of death from any bacterial agent (15,22). Mycobacterium tuberculosis and nontuberculous mycobacteria (NTM) are different clinically, so prompt detection, isolation, and discrimination are essential for appropriate management (3, 7).…”
mentioning
confidence: 99%
“…Tuberculosis is a global problem and the single most common cause of death from any bacterial agent (15,22). Mycobacterium tuberculosis and nontuberculous mycobacteria (NTM) are different clinically, so prompt detection, isolation, and discrimination are essential for appropriate management (3,7).…”
mentioning
confidence: 99%
“…Because optimization of pharmacokinetic properties is frequently a rate limiting step in the preclinical development of anti-tuberculosis agents (10)(11)(12), the pharmacokinetically-guided lead optimization used in this publication may also be useful for screening other compounds in early drug discovery projects.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis is a global problem and the single most common cause of death from any bacterial agent (Laughon, 2007;Park et al, 2009;WHO, 1996) Mycobacterium tuberculosis (MTB) and NTM are different clinically, therefore rapid detection, isolation, and discrimination are essential for appropriate management (ATS, 1997; Hasegawa et al, 2002;Park et al, 2009).…”
Section: Introductionmentioning
confidence: 99%